Synthesis and Cytotoxic Activity of Methoxylated Chalcones in Breast Cancer MCF-7 and Prostate Cancer DU-145 Cell Lines - Fareza, Muhamad Salman; Samudra, Genta Hafied Naga; Asrada, Syahdan; Fischellya, Dafi; Wijaya, Triyadi Hendra; Choironi, Nur Amalia; Wasito, Hendri; Suhesti, Tuti Sri; Mustikaningtyas, Ika; Rehana, Rehana; Setiyabudi, Lulu; Sarmoko, Sarmoko (Molekul, 2025)
Chalcones, a class of naturally occurring compounds, exhibit a broad spectrum of biological activities, including anticancer properties. In this study, a series of methoxylated chalcones were synthesized via Claisen-Schmidt condensation and evaluated for cytotoxic activity against breast cancer MCF-7 and prostate cancer DU-145 cell lines. The synthetic route involved Claisen-Schmidt condensation, leading to various methoxy-substituted chalcone derivatives. The structures of the synthesized chalcones were confirmed through NMR and mass spectrometry. Cytotoxicity was assessed using the PrestoBlue assay, with 4-bromochalcone (compound 2) displaying the highest cytotoxic activity against MCF-7 cancer cell lines (IC50 = 26.99 µM). These results indicate that methoxylated chalcones hold promise as potential lead compounds for the development of new anticancer agents targeting breast and prostate cancer.